Correlation Between Systemic Inflammation, Gut Microbiome Dysbiosis and Postoperative Complications After the Modified Whipple Procedure - Gelu Mihai Breaza; Florin Emil Hut; Octavian Cretu; Simona-Alina Abu-Awwad; Ahmed Abu-Awwad; Laurențiu Vasile Sima; Radu Gheorghe Dan; Cristina Ana-Maria Dan; Raluca Maria Closca; Flavia Zara (Biomedicines)
(1) Background: The modified Whipple procedure, or pylorus-preserving pancreaticoduodenectomy, is a complex surgical intervention used to treat pancreatic head tumors. While preserving digestive function, it is associated with significant perioperative risks. This study explores the clinical, immunological, and microbiome-related factors influencing postoperative complications, focusing on the interplay between patient comorbidities, systemic inflammation, and gut dysbiosis. (2) Methods: A retrospective analysis was conducted on 123 patients undergoing the modified Whipple procedure for pancreatic head tumors. Patients were categorized into two groups based on the occurrence of significant postoperative complications (Group A: with complications; Group B: without complications). Data on demographics, comorbidities, inflammatory markers (CRP, IL-6, procalcitonin), and gut microbiome composition were collected. Microbial diversity was evaluated using the Shannon Index, and logistic regression was performed to identify independent predictors of complications. (3) Results: Patients in Group A had a significantly higher prevalence of diabetes mellitus (43.1% vs. 20.8%; p = 0.02) and cardiovascular disease (35.3% vs. 13.9%; p = 0.01). Elevated inflammatory markers (CRP ≥ 40 mg/L, IL-6 ≥ 30 pg/mL, procalcitonin ≥ 0.5 ng/mL) were strongly associated with higher complication rates. Microbiome analysis indicated dysbiosis in Group A, with reduced Lactobacillus and Bifidobacterium levels, increased Enterobacteriaceae abundance, and a lower Shannon Index (<2). Patients exhibiting both dysbiosis and elevated inflammation had the highest complication rate (60%). Multivariate analysis identified diabetes, elevated IL-6, and dysbiosis as independent predictors of adverse outcomes. (4) Conclusions: Postoperative complications after the modified Whipple procedure are influenced by systemic inflammation and gut dysbiosis. A systematic preoperative assessment of microbiome health and inflammatory markers enables accurate risk stratification and personalized interventions, potentially reducing the incidence of complications and improving overall surgical outcomes.